2012
DOI: 10.1108/14720701211191328
|View full text |Cite
|
Sign up to set email alerts
|

UK audit committees and the Revised Code

Abstract: UK audit committees and the Revised CodePurpose: The audit committee is one of the most prominent board subcommittees, having a potentially important role to play in ensuring sound corporate governance. This paper examines and discusses the behaviour of companies following revisions to the UK's Revised Code.Research design/methodology/approach: A variety of annual report data from a sample of 50 UK companies, stratified according to size, is collected and analyzed.Findings: General compliance with many provisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Section 2 of SOX (2002) elaborates an AC as, "a committee (or equivalent body) established by and amongst the BOD of an issuer to oversee the accounting and financial reporting processes of the issuer and audits of the financial statements of the issuer." Research regarding ACs measures their ability to effectively monitor the formulation of financial reports and reduce the chances of EM in three dimensions, which are: Its financial expertise [40,76], its independence [77,78], and its frequency of meetings [77,79]. In [76], the authors investigated the impact of AC expertise on audit quality, and the results suggest that both specialist and non-specialist financial experts influence the audit quality, however in different ways.…”
Section: Financial Expertise Of Audit Committeementioning
confidence: 99%
“…Section 2 of SOX (2002) elaborates an AC as, "a committee (or equivalent body) established by and amongst the BOD of an issuer to oversee the accounting and financial reporting processes of the issuer and audits of the financial statements of the issuer." Research regarding ACs measures their ability to effectively monitor the formulation of financial reports and reduce the chances of EM in three dimensions, which are: Its financial expertise [40,76], its independence [77,78], and its frequency of meetings [77,79]. In [76], the authors investigated the impact of AC expertise on audit quality, and the results suggest that both specialist and non-specialist financial experts influence the audit quality, however in different ways.…”
Section: Financial Expertise Of Audit Committeementioning
confidence: 99%
“…Independence is one of the most important characteristics of an audit committee. It is a requirement that an audit committee be free from the influence of senior management (Jun Lin & Tang, 2008;Avison & Cowton, 2012;Larry & Taylor, 2012). Independent audit committees are capable of resisting pressure from management (Al-Matari, 2013;.…”
Section: Audit Committee Independencementioning
confidence: 99%
“…Of specific relevance to this research is the work conducted by Avison and Cowton (2012) in which they examined the extent of compliance of British companies towards the revised code of corporate governance. Their findings show that some of the firms have not followed some of the recommended practices stated in the revised code, such as the fixed number of non-executive directors on the audit committees.…”
Section: Corporate Governance Attributes In Malaysiamentioning
confidence: 99%
“…This could to some extent be due to different governance structures, timeframes, and cultures examined by previous studies. Of particular importance to this study is the work conducted by (Avison and Cowton, 2012), which investigated compliance by corporations with the amended code of corporate governance in the UK. The study found that some of the firms involved have not followed some of the recommended practices stressed in the revised code such as the required number of non-executive directors on the audit committees.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation